2016
DOI: 10.4274/turkderm.78477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life in patients with genital warts

Abstract: Background and Design: Genital warts, a very common sexually-transmitted infection, negatively affect the quality of life of patients especially from the psychosocial point of view. In this study, we aimed to investigate the effects of genital warts on the quality of life by comparing patient and control groups. Materials and Methods: Eighty patients and 75 healthy individuals were included in the study. The 36-item Short-form health survey and Dermatology life quality index (DLQI) were administered to patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
3
0
9
Order By: Relevance
“…17,18 The reason was that severe anxiety and stress were more frequent in women, they were concerned more about how they are looking and they were more sensitive to changes in quality of life. 19 In our study, we observed that pruritus was more frequent in women and affected more quality of life than man.…”
Section: Discussionmentioning
confidence: 58%
“…17,18 The reason was that severe anxiety and stress were more frequent in women, they were concerned more about how they are looking and they were more sensitive to changes in quality of life. 19 In our study, we observed that pruritus was more frequent in women and affected more quality of life than man.…”
Section: Discussionmentioning
confidence: 58%
“…Generické nástroje k hodnocení kvality života související se zdravím v několika zahraničních studiích ukázaly, že pacienti s CA mají sníženou QOL (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Tyto generické nástroje nejsou ovšem optimalizovány pro hodnocení sexuální, psychologické a emocionální oblasti QOL pacientů s CA.…”
Section: Discussionunclassified
“…3 Yayımlanmış birçok çalışma, genital siğillerin farklı popülasyonlarda etkilenen bireylerin psikolojik iyilik ve yaşam kalitesi üzerindeki olumsuz etkilerini vurgulamaktadır. [4][5][6][7][8][9] Öte yandan, günlük pratiğimizde ekstragenital siğillerin görülme sıklığı, hastalarımız için yaşam kalitesi üzerindeki etkisini tanımlama ihtiyacını haklı çıkarmaktadır. Bu çalışma ile çoklu ekstragenital siğillerin dermatoloji yaşam kalitesine olan etkisini bulmayı hedefledik.…”
unclassified
“…15 Yine benzer şekilde çeşitli merkezlerde farklı anketler kullanılarak yapılan çalışmalarda, genital siğilin yaşam kalitesi üzerine olumsuz etkileri gösterilmiş; hastalarda psikososyal anlamda ve cinsel yaşamda bozulmaya neden olduğu bildirilmiştir. [4][5][6][7][8][9]16,17 Erdem ve ark.nın çalışmasında da aynı şekilde genital siğili olan hastaların yaşam kalitelerinin negatif yönde etkilendiği gösterilmiştir. 9 Grupların sorulara verdiği yanıtlara baktığımızda, bazı sorularda anlamlı farklar göze çarpmaktaydı.…”
unclassified
See 1 more Smart Citation